2021
DOI: 10.3390/ijms22136727
|View full text |Cite
|
Sign up to set email alerts
|

Monosomy 3 Is Linked to Resistance to MEK Inhibitors in Uveal Melanoma

Abstract: The use of MEK inhibitors in the therapy of uveal melanoma (UM) has been investigated widely but has failed to show benefits in clinical trials due to fast acquisition of resistance. In this study, we investigated a variety of therapeutic compounds in primary-derived uveal melanoma cell lines and found monosomy of chromosome 3 (M3) and mutations in BAP1 to be associated with higher resistance to MEK inhibition. However, reconstitution of BAP1 in a BAP1-deficient UM cell line was unable to restore sensitivity t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…Hence, all of these points explain the move towards dual therapies against Gαq/11 that prevent rebound activation of such alternative proliferative signalling pathways, with the undesirable drawback of increased toxicity [76]. Similarly, certain chromosomal alterations and gene mutations were associated with resistance to the action of these targeted therapies, such as the relationship observed between M3 and decreased sensitivity to MEK inhibition [119]. The role of these alternative genetic alterations in the effectiveness of drugs targeting downstream GNAQ/GNA11 signalling pathways could support the idea that these genes are not really involved in UM prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, all of these points explain the move towards dual therapies against Gαq/11 that prevent rebound activation of such alternative proliferative signalling pathways, with the undesirable drawback of increased toxicity [76]. Similarly, certain chromosomal alterations and gene mutations were associated with resistance to the action of these targeted therapies, such as the relationship observed between M3 and decreased sensitivity to MEK inhibition [119]. The role of these alternative genetic alterations in the effectiveness of drugs targeting downstream GNAQ/GNA11 signalling pathways could support the idea that these genes are not really involved in UM prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…RNA extraction was performed using a Qiagen RNeasy kits, according to manufacturer´s instructions, and cDNA was synthesized from 1 μg of total RNA in all samples with a QuantiTect Reverse Transcription kit (Qiagen). qRT-PCR was performed as in ( Mergener et al, 2021 ), using primers published elsewhere ( Peña-Llopis et al, 2011 ).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the UCH catalytic domain, BAP1 contains a UCH37-like domain, binding domains for BRCA1 and BARD1, and a binding domain for HCFC1. BAP1 forms a tumor suppressor heterodimeric complex with BRCA1 and BARD1 that is involved in cell proliferation, DNA damage response, and differentiation processes through influencing chromatin remodeling [ 46 , 73 ]. The binding of BAP1 with HCFC1 interacts with histone-modifying complexes [ 46 ].…”
Section: Genetic Landscapementioning
confidence: 99%
“…Other trials included in the review were for trametinib monotherapy [ 132 , 133 ], trametinib with uprosertib (AKT inhibitor) [ 132 ], and binimetinib with sotrastaurin (PKC inhibitor) (NCT01801358). Mergener et al demonstrated that BAP1 mutations and monosomy 3 were associated with higher resistance to MEK inhibition [ 73 ]. Their analysis suggested that these tumors with BAP1 mutation are more resistant to MEK inhibitors because downregulation of eukaryotic translation initiation factor 2A (EIF2A) seen in BAP1 mutated tumors may lead to a decrease in ribosome biogenesis while inducing an adaptive response to stress [ 73 ].…”
Section: Treatment Based On Mutational Profilementioning
confidence: 99%